1995
DOI: 10.1002/bies.950170906
|View full text |Cite
|
Sign up to set email alerts
|

DNA topoisomerase II mutations and resistance to anti‐tumor drugs

Abstract: Mutations in DNA topoisomerase II are often correlated with drug-resistance in tumor cell lines. Studies of topoisomerase II-mediated drug-resistance in various model systems, as well as the sequencing of such mutations from drug-resistant tumors, have shed light on the functional domains of topoisomerase II, on how it interacts with inhibitors, and on the different mechanisms by which cells avoid the toxic effects of many clinically important anti-tumor drugs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0
1

Year Published

1996
1996
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(36 citation statements)
references
References 54 publications
2
33
0
1
Order By: Relevance
“…[37][38][39] This is also the case with BTZ resistance; we and others have reported mutations in the b5 subunit in pre-clinical BTZ-resistant cell line models. 20,21,34,40 In this study, we identified four novel mutations, all residing within the BTZbinding pocket, and cluster with the previously reported G322A (Ala49Thr) 20,21,40 and C323T (Ala49Val) 34 mutations.…”
Section: Discussionmentioning
confidence: 99%
“…[37][38][39] This is also the case with BTZ resistance; we and others have reported mutations in the b5 subunit in pre-clinical BTZ-resistant cell line models. 20,21,34,40 In this study, we identified four novel mutations, all residing within the BTZbinding pocket, and cluster with the previously reported G322A (Ala49Thr) 20,21,40 and C323T (Ala49Val) 34 mutations.…”
Section: Discussionmentioning
confidence: 99%
“…We now believe that this is incorrect. All available evidence indicates that non-covalent topoisomerase II poisons act within the active site of the enzyme at the interface between the protein and DNA substrate [15,16,[133][134][135][136][137]. Furthermore, mechanistic studies suggest that it is actually the interactions between topoisomerase II and these compounds that serve as the point of entry into the enzyme-DNA complex [135][136][137][138].…”
Section: Non-covalent Topoisomerase II Poisonsmentioning
confidence: 99%
“…Although topoisomerase II-targeted anticancer drugs act at the enzyme-DNA interface [15,16,104,[133][134][135][136][137], the accumulation of drugs in the double helix has the potential to inhibit enzyme binding or activity. Because the generation of positive superhelical twists by DNA intercalation induces torsional stress in the double helix [130,189], the ability of these molecules to absorb intercalative compounds is limited.…”
Section: Effects Of Dna Supercoiling On Topoisomerase Ii-mediated Dnamentioning
confidence: 99%
“…[20][21][22][23][24][25] In addition, in some particular cell lines, topoisomerase II gene mutations have been identified and suggested to be responsible for the reduced drug sensitivity to DNA topoisomerase inhibitors. [26][27][28][29] Conversely, more recent studies have shown that increasing the intracellular level of the enzyme by transfection of topoisomerase genes can restore the sensitivity of resistant cancer cell lines to DNA topoisomerase inhibitors. [30][31][32][33][34] On the other hand, anthracyclines are wellknown chemotherapeutic agents that can cause cardiotoxicity in clinical use.…”
Section: Introductionmentioning
confidence: 99%